Emerging Paradigm of Edge Computing in the Context Of Iot - SHIRISHA, BETHALA; DIVYA PRIYA, DEGALA; ., MAHALAKSHMI; REDDY CHILUKALA, MAHENDER; PRAVALLIKA, BETHALA (International Journal of Engineering and Technology, 2018)
Centralised Cloud computing is having many challenges with the rapid increasing in IoT( Internet Of Things) applications. The challenges are high latency, low spectral efficiency (SE), and non-adaptive machine type of communication. In order to solve these challenges have moved to the concept of new computing concept that is nothing but edge computing, which calls for moving the data at the edge of the network. Edge computing has the possible to deal with the concerns of battery life constraint, response time requirement, data safety, bandwidth cost saving and privacy. In this paper, we started the explanation with IoT and solution of IOT i.e. edge computing, followed by several case studies, ranging from cloud offloading to smart home and city, as well as collaborative edge to materialize the concept of edge computing.Â Â